Eksistensi dan Perlindungan Hak Atas Harta Benda dalam Sistem Hukum Nasional dan Hukum Internasional - Setiawan, Risman (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
The right to property is a fundamental part of human rights that guarantees every individual the right to legally own, use, and enjoy the fruits of ownership. In the context of the Indonesian national legal system, this right is constitutionally based through Article 28H paragraph (4) of the 1945 Constitution of the Republic of Indonesia, which affirms that everyone has the right to own property and that it may not be arbitrarily confiscated. The existence of the right to property is not only derived from national provisions, but is also recognized in various international legal instruments such as the Universal Declaration of Human Rights (UDHR) and the International Covenant on Civil and Political Rights (ICCPR). However, the implementation of its protection still faces challenges, including in terms of law enforcement, ownership conflicts, and development policies that have the potential to ignore individual rights to property. Through a normative and comparative-juridical approach, this study examines how the national legal system attempts to balance individual interests and public interests in protecting the right to property, while ensuring its compliance with human rights principles